2022
DOI: 10.1097/jsm.0000000000001060
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Policy Prohibiting Body Checking on Physical Contacts in U15 and U18 Youth Ice Hockey Leagues

Abstract: To compare physical contacts (PCs) and head contacts (HCs) in nonelite U15 (ages 13-14) and U18 (ages 15-17) ice hockey players in body checking (BC) and non-BC leagues. Design: Cohort video analysis study. Setting: Ice hockey arenas in Calgary, Canada. Participants: Players from 13 BC and 13 non-BC games at the nonelite U15 and U18 levels (n 5 52 total games). Assessment of Risk Factors: Games were videotaped and analyzed to compare PC variables between leagues allowing and prohibiting BC. Main Outcome Measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(36 reference statements)
0
1
1
Order By: Relevance
“…This contradicts previous research comparing BC with non-BC male youth ice hockey, where disallowing BC decreased the overall HC IR by 60% in U15 leagues. 28 However, Kolstad et al's study also found a 50% lower total PC IR in leagues disallowing BC, whereas our study found only a 13% lower PC IR in female leagues where BC is disallowed. Interestingly, the total HC IRs in the female games (IR 5 13.5/100 team-minutes, 95% CI: 11.4-16.0) were higher than that reported in Canadian female varsity ice hockey (IR 5 10.67/100 team-minutes, 95% CI: 8.28-13.75).…”
Section: Ra Williamson Et Al (2023)contrasting
confidence: 78%
See 1 more Smart Citation
“…This contradicts previous research comparing BC with non-BC male youth ice hockey, where disallowing BC decreased the overall HC IR by 60% in U15 leagues. 28 However, Kolstad et al's study also found a 50% lower total PC IR in leagues disallowing BC, whereas our study found only a 13% lower PC IR in female leagues where BC is disallowed. Interestingly, the total HC IRs in the female games (IR 5 13.5/100 team-minutes, 95% CI: 11.4-16.0) were higher than that reported in Canadian female varsity ice hockey (IR 5 10.67/100 team-minutes, 95% CI: 8.28-13.75).…”
Section: Ra Williamson Et Al (2023)contrasting
confidence: 78%
“…27 However, when comparing with nonelite U15 male ice hockey leagues that also prohibit BC (divisions 4-7, lowest 60% by division of play), elite female ice hockey had nearly double the player-to-player PCs coded using the same validated videoanalysis techniques (1661 total PCs over 13 male non-BC games, 127.8 PCs/game vs 3861 total PCs over 10 female non-BC games, 386.1 PCs/game). 28 These findings reveal that female youth ice hockey is a physical sport, and opportunities for future injury prevention are warranted. Head contacts are the most common mechanism of concussion, one of the most common injuries reported in youth sports and specifically ice hockey.…”
Section: Ra Williamson Et Al (2023)mentioning
confidence: 91%